The Potential of Use Artificial Intelligence in Implementing Character Education in Arabic Language Subjects - Gunawan, Riski; Hidayatullah, Muhammad Subkhi (Asalibuna, 2024)
This study aims to examine one approach to addressing the nation's character issues by utilizing artificial intelligence as a means to instill character values in Arabic language learning. The research method used in this study is literature review, focusing on the latest scientific studies from the past five years, with the subjects being artificial intelligence, character education, and Arabic language. The findings of this study indicate that artificial intelligence, commonly used as a tool for Arabic language learning, has the potential to be optimized for character education during the learning process. From the study's results, it is concluded that this approach can be implemented by utilizing artificial intelligence as an aid in creating Arabic language learning content, which includes both explicit skills and hidden character values. Therefore, students using this material are expected to be encouraged to develop positive personalities and characters, thus reducing bullying or other misbehavior among students.